Effect of Ultrasonic Application during Friction Stir Welding on Microstructure and Properties of AA2024 Fixed Joints; Key Engineering Materials; Vol. 683 : Multifunctional Materials: Development and Application - Eliseev A. Aleksandr Andreevic; Tarasov S. Yu. Sergei Yulievich; Fortuna S.; Rubtsov V. E. Valery Evgenjevich; Kalashnikova T. A. Tatiana Alexandrovna (Physicochemical Properties of Materials and Current Processing Technologies, 2016)
Title screen